Relationship Between Summer Precipitation in North China and Madden–Julian Oscillation During the Boreal Summer of 2018 - Hao, Lisheng; He, Liye; Ma, Ning; Liang, Sujie; Xie, Jun (Frontiers in Earth Science, 2020)
Based on the data regarding summer precipitation in North China, the tropical Madden–Julian Oscillation (MJO) index (meaning the “All-Season Real-Time Multivariate MJO index,” abbreviated as RMM1 and RMM2), and National Centers for Environmental Prediction (NCEP)/National Center for Atmospheric Research (NCAR) reanalysis data, this paper analyzed the relationship between the summer precipitation of 2018 in North China and MJO by applying multiple statistical methods. Findings indicate that (1) summer precipitation in North China is closely related to MJO. When MJO was in phases 5 and 6, North China had heavy precipitation. (2) The correlation mechanism is primarily as follows: At 850 hPa, when MJO storm clouds move eastward, anticyclonic circulation is stimulated in the north side of the convection area, thus forming a pair of cyclones and anticyclones. Although MJO storm clouds cannot move northward to higher latitudes to have a direct impact on the summer precipitation in North China, when MJO moves eastward into phases 5 and 6, the anticyclonic circulation on the north side of cyclones can strengthen the water-vapor transmission by southerly wind for RMM1 or by southeast wind for RMM2 in summer in North China thus providing favorable water-vapor conditions for precipitation in North China. At 500 hPa, when MJO moves eastward into phases 5 and 6, the western Pacific subtropical high will move northward to the area near the Korean Peninsula and be strengthened, thus blocking weather systems that come from the west, and facilitating ascending motions in North China. (3) MJO can be used for the extended-range forecasting of summer precipitation over North China.